EXOGEN Mitigates Risk of Fifth Metatarsal Fracture Nonunion: Results of a Novel Real-World Clinical Study. Issue 1 (January 2022) - Zura, Robert; Anderson, Robert B.; Ahmed, Sonya S.; Hak, David; Watson, Tracy; Mack, Christina; Irwin, Debra E.; Maislin, Greg; Kelly, Kim P.; Jones, John T.; Wester, Tawana; Pavesio, Alessandra; et al.
Category: Midfoot/Forefoot Introduction/Purpose: Fifth metatarsal fractures are the most commonly fractured metatarsal in adults and are associated with high rates of nonunion. This study compared the 9-month incidence of nonunion in fifth metatarsal fracture patients using EXOGEN (Bioventus LLC), low-intensity pulsed ultrasound, versus a control cohort of patients receiving standard of care. Methods: Adults (21-80 years) prescribed EXOGEN for any acute or delayed fifth metatarsal fracture and initiated treatment within 91 days of the fracture were enrolled via prescription record abstraction and direct-to-patient outreach. Open, closed, surgically repaired and conservatively managed fractures were eligible. Jones' fractures consisted of 31.2% of the overall EXOGEN population. EXOGEN treatment compliance was assessed using patient self-report and the device's software. A control cohort of patients with the same eligible fractures were extracted from the MarketScan TM national insurance database (IBM Watson Health). Propensity score (PS) modeling accounting for demographics, comorbidities, concomitant medication, and type of fracture/fracture treatment was used to address potential selection bias via three methods: subclassification, 1:1 matching on individual covariates, and PS weighting. Effectiveness was compared for 1, 943 EXOGEN and 10, 259 controls. Study endpoint was based on presence or absence of an ICD-10-CM nonunion diagnosis code in the medical billing records for both groups. Results: Matched MarketScan controls had a clinically and statistically significant increase in risk of nonunion compared to patients who used EXOGEN for at least 90 total once-daily treatments (McNemar's OR = 1.67; p=0.048). Results improved with more treatments; the nonunion risk was 2.44 times (p=0.0239) and 5.00 times (p=0.008) for the control patients than EXOGEN patients with at least 120 and 140 total treatments, respectively. The nonunion rate was reduced by over half in Jones' fracture patients treated with at least 90 total once-daily EXOGEN treatments (n=269; 3.3%) as compared to those not reaching this minimum threshold (n=337, 6.8%); such results approached statistical significance (p=0.057). Analyses of the treatment effect by nonunion risk factors showed EXOGEN attenuated the effect of many of these factors on nonunion rates. Early treatment was found beneficial; treatment delay was associated with increased nonunion risk of ~20% for every 15 days of latency 45 days post- fracture. Conclusion: In this large external comparator study, EXOGEN was found to be effective in mitigating the risk of nonunion in fifth metatarsal fracture patients when used for a minimum of 90 total treatments, even in the presence of many nonunion risk factors. Treatment should be initiated as soon as possible following fracture (at least by 45 days post-fracture) to further reduce the risk of nonunion.